2016
DOI: 10.1186/s40174-016-0057-2
|View full text |Cite
|
Sign up to set email alerts
|

Job loss by wage level: lessons from the Great Recession in Ireland

Abstract: This paper explores the incidence of job loss by wage level during the Great Recession, using data for Ireland. Ireland experienced a particularly pronounced decline in employment by international and historical standards, which makes it a valuable case study. Using EU Survey on Income and Living Conditions (EU-SILC) data, our analysis reveals that the probability that an employee remains in employment, from one year to the next, is positively related to their monthly earnings during both boom and bust. The gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…10 CSO data show employment in the relatively low skilled construction sector fell from 225,100 in 2005 to 103,300 in 2012. These unemployment data are consistent with recent work by Nolan and Voitchovsky (2016) who used the EU-SILC data to examine job loss by wage level during the Great Recession. They found that the probability that an employee remains in employment from one year to the next is positively related to their monthly earnings during both the boom and the recession.…”
Section: B Compositional Changes: Unemployment Cohort Effects and Migrationsupporting
confidence: 87%
See 2 more Smart Citations
“…10 CSO data show employment in the relatively low skilled construction sector fell from 225,100 in 2005 to 103,300 in 2012. These unemployment data are consistent with recent work by Nolan and Voitchovsky (2016) who used the EU-SILC data to examine job loss by wage level during the Great Recession. They found that the probability that an employee remains in employment from one year to the next is positively related to their monthly earnings during both the boom and the recession.…”
Section: B Compositional Changes: Unemployment Cohort Effects and Migrationsupporting
confidence: 87%
“…Callan et al (2014) examined income inequality from 2008-2013 and found that the largest falls in market income occurred in the bottom half of the income distribution. Much of this reflects the loss of earnings resulting from job losses which were most pronounced among the lower paid (Nolan and Voitchovsky, 2016). Callan et al (2014) focused their analysis on the distribution of total household income and on the impact of changes in the tax benefit system on this distribution.…”
Section: The Great Recessionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same paper by Nolan and Voitchovsky (2016) showed that in Ireland the positive correlation between workers’ monthly earnings and the probability of remaining in employment was higher during the ‘bust’ period (2009) compared with the boom year (2006). Bachmann et al (2015) investigated the heterogeneous effects of the Great Recession (2008–2010) on labour market transitions in Europe by sociodemographic group and employment type.…”
Section: Related Literaturementioning
confidence: 96%
“…In relation to the first aspect, Nolan and Voitchovsky (2016) investigated the incidence of job loss by job quality levels (wage quintiles) in Ireland. The analysis, which was based on EU Survey on Income and Living Conditions (EU-SILC) cross-sectional data for employees in 2006 and 2009, showed that the probability of remaining in employment is positively correlated with monthly earnings, after controlling for a series of individual and household variables which may affect labour market circumstances.…”
Section: Related Literaturementioning
confidence: 99%